Implementasi Regulasi Standar Pendidik Berwawasan Merdeka Belajar Kampus Merdeka Pada PTKI Jawa Timur - Fauziah, Fauziah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2023)
Until now the management of educator standards has not been effective because the recruitment process is not selective and competency development has not been carried out properly so that strategic steps are needed to develop it especially in implementing MBKM in higher education which requires the right steps. The purpose of this study was to analyze the management of educator standards in implementing MBKM at PTKI East Java. The approach used in this study is a qualitative approach with a multi-case study type at UIN Maulana Malik Ibrahim Malang, IAIN Kediri and Zainul Hasan Genggong University, Probolinggo. The data were obtained from statements from leaders or policy makers orally and documentation of the management of educator standards at PTKI East Java The research results show that the implementation of standard regulations for MBKM-oriented educators at PTKI East Java is carried out based on Law no. 14 of 2005 concerning Teachers and Lecturers, and its implementation in the recruitment of lecturers and the development of their competencies and qualifications that can carry out the MBKM program which is carried out in the form of socialization and training to provide a complete picture of lecturers’ readiness in facilitating independent learning.